Experimental investigation of the gas desorption–diffusion behavior of multi-scale outburst-prone coal under constant desorption pressures - Chaojun Fan; Rui Zhu; Lei Yang; Mingkun Luo; Xiang Fu; Xuan Liu; Xiaofeng Jiang (Chemical Engineering Journal, 2026)

Genome-wide methylation and transcriptome analysis in koi carp (Cyprinus carpio var. koi): Uncovering novel molecular mechanisms in skin color differentiation and pigmentation - Xiulan Shi; Xiaoyu Chen; Wenbin Zhu; Jun Guo; Kai Lin; Jianjun Fu; Lanmei Wang; Mingkun Luo; Zaijie Dong (Aquaculture, 2026)

Evaluation of muscle quality and movement-related traits in two common carp strains under a rice–fish farming system - Yating Gong; Mingkun Luo; Xianbo Zhang; Ning Qin; Wenbin Zhu; Lanmei Wang; Jianjun Fu; Zaijie Dong (Aquaculture International, 2025)

Effects of temperature on growth performance, gonad development, immunity, and antioxidant response of hybrid red tilapia (Oreochromis niloticus ♂ × Oreochromis aureus ♀) - Endalh Mekonnen; Yujie Deng; Yude Sun; Lanmei Wang; Jianjun Fu; Mingkun Luo; Zaijie Dong; Wenbin Zhu (Aquaculture International, 2025)

Genome-wide association study reveals candidate genes critical for skin pigmentation in common carp (Cyprinus carpio) strains including koi - Xiulan Shi; Wenbin Zhu; Jun Guo; Kai Lin; Jianjun Fu; Lanmei Wang; Yalun Dong; Mingkun Luo; Zaijie Dong (Aquaculture, 2024)

Molecular characterization and function of hif1a and fih1 in response to acute thermal stress in American shad (Alosa sapidissima) - Zhengyuan Liang; Songqin Hu; Yalun Dong; Linghong Miao; Wenbin Zhu; Bingbing Feng; Jianjun Fu; Mingkun Luo; Lanmei Wang; Zaije Dong (Fish Physiology and Biochemistry, 2024)

Development, Comparison, and Qualification of Predictive Pharmaceutical Stability Models Using Independent Statistical Tools - Mingkun Fu; Andrea Orta; Robert Bujalski; Jennifer Greene; Lakshminarasimhan Pranatharthiharan (Journal of Pharmaceutical Innovation, 2024)

To improve the performance of GPS single point positioning under flood environment based on multi-CNR weight strategy and multipath mitigation - Xiaoliang Shen; Mingkun Su; Jun Wu; Junna Shang; Chao Wu; Fu Zheng (Advances in Space Research, 2024)

Environment change recorded by lake sediment magnetism in the Songnen Plain, northeastern China - Huan Fu; Mingkun Li; Kunshan Bao; Yongdong Zhang; Tingping Ouyang (Science of The Total Environment, 2024)

Science- and Risk-Based Stability Strategies to Support Product Lifecycle Changes - Lori McCaig; Steven Nowak; Alexander Abbott; Jenny Carhart; Megan E. McMahon; Elke Debie; Hanlin Li; Francis Maina; Andrea J. Ji; Mingkun Fu; Yan Wu; Andrew Lennard; et al. (The AAPS Journal, 2024)

High-temperature stress response: Insights into the molecular regulation of American shad (Alosa sapidissima) using a multi-omics approach - Mingkun Luo; Wenbin Zhu; Zhengyuan Liang; Bingbing Feng; Xudong Xie; Yulin Li; Ying Liu; Xiulan Shi; Jianjun Fu; Linghong Miao; Zaijie Dong (Science of The Total Environment, 2024)

Deep spatiotemporal transcriptome analysis provides new insights into early development of koi carp (Cyprinus carpio var. koi) - Mingkun Luo; Xiulan Shi; Jun Guo; Kai Lin; Wenbin Zhu; Jianjun Fu; Lanmei Wang; Zaijie Dong (Aquaculture, 2023)

Integrative analysis uncovers the mechanism underlying the environmental adaptation of an indigenous crucian carp (Carassius auratus gibelio) in Dong's Rice Fish Duck System - Mingkun Luo; Xianbo Zhang; Wenbin Zhu; Qianwen Min; Jinli Hu; Jianjun Fu; Xiulan Shi; Bingjie Jiang; Yating Gong; Lanmei Wang; Ting Liu; Zaijie Dong (Aquaculture, 2023)

Integrating decision-making preferences into ecosystem service conservation area identification: A case study of water-related ecosystem services in the Dawen River watershed, China - Kai Li; Ying Hou; Qi Fu; Mark Taylor Randall; Peter Stubkjær Andersen; Mingkun Qiu; Hans Skov-Petersen (Journal of Environmental Management, 2023)

Screening and Identification of Interacting Proteins of Mitfa in Red Tilapia - Bingjie Jiang; Lanmei Wang; Jianjun Fu; Wenbin Zhu; Mingkun Luo; Zaijie Dong (Fishes, 2023)
Skin color variation and differentiation are bottlenecks in the aquaculture industry of red tilapia. The mitfa gene primarily regulates melanocyte survival and proliferation in fish skin pigmentation. In this study, a recombinant expression vector for Mitfa expression was successfully constructed. After induction and purification, nearly 600 μg of Mitfa protein was purified from the fermentation supernatant. His pull-down assay, followed by LC-MS/MS analysis, revealed 10 proteins that interact with the Mitfa protein. Five of these proteins were annotated in the melanogenesis and tyrosine metabolism pathways, including Krt, Tpm, Myh, Tyr and Dct. The purified Mitfa recombinant protein was injected into red tilapia, and its activity and function were examined. The expression levels of the mitfa, tyr, tyrp1, and dct genes increased greatly in the dorsal skin after injection (p

Influence of flooding on GPS carrier-to-noise ratio and water content variation analysis: a case study in Zhengzhou, China - Mingkun Su; Fu Zheng; Junna Shang; Lei Qiao; Zhaoyang Qiu; Huan Zhang; Jiansheng Zheng (GPS Solutions, 2023)

Correction to: Transcriptome analysis of skin color variation during and after overwintering of Malaysian red tilapia - Bingjie Jiang; Lanmei Wang; Mingkun Luo; Jianjun Fu; Wenbin Zhu; Wei Liu; Zaijie Dong (Fish Physiology and Biochemistry, 2022)

Transcriptome analysis of skin color variation during and after overwintering of Malaysian red tilapia - Bingjie Jiang; Lanmei Wang; Mingkun Luo; Jianjun Fu; Wenbin Zhu; Wei Liu; Zaijie Dong (Fish Physiology and Biochemistry, 2022)

Identification and characterization of 76 SNP markers in the large-scale loach (Paramisgurnus dabryanus) by using SLAF sequencing - Jianjun Fu; Shunpeng Wan; Wenbin Zhu; Lanmei Wang; Mingkun Luo; Xianhu Zheng; Zaijie Dong (Conservation Genetics Resources, 2022)

Correction to: Considerations for Updates to ICH Q1 and Q5C Stability Guidelines: Embracing Current Technology and Risk Assessment Strategies - Megan E. McMahon; Alexander Abbott; Yelizaveta Babayan; Jenny Carhart; Chi-wan Chen; Elke Debie; Mingkun Fu; Cherokee Hoaglund-Hyzer; Andrew Lennard; Hanlin Li; Tony Mazzeo; Lori McCaig; et al. (The AAPS Journal, 2021)

Considerations for Updates to ICH Q1 and Q5C Stability Guidelines: Embracing Current Technology and Risk Assessment Strategies - Megan E. McMahon; Alexander Abbott; Yelizaveta Babayan; Jenny Carhart; Chi-wan Chen; Elke Debie; Mingkun Fu; Cherokee Hoaglund-Hyzer; Andrew Lennard; Hanlin Li; Tony Mazzeo; Lori McCaig; et al. (The AAPS Journal, 2021)

Lean Stability Case Studies—Leveraging Science- and Risk-Based Approaches to Enable Meaningful Phase Specific Pharmaceutical Stability Strategies - Eric Adamec; Yelizaveta Babayan; Bruno Catacchio; Angela Coon; Allison Dill; Mingkun Fu; Lars Gruenig; Cherokee Hoaglund Hyzer; Michael Lesslie; Megan McMahon; Donnie Pulliam; Fenghe Qiu; et al. (Journal of Pharmaceutical Innovation, 2021)
Purpose Lean stability is a science- and risk-based initiative which utilizes the enhanced understanding of drug substance and drug product physical and chemical characteristics to (1) reduce and optimize the design of standard stability protocols; (2) expedite the generation of stability data without impact to safety, efficacy, or quality of the product; and (3) decrease time to market for innovative drugs. Lean stability was introduced in the early 2000s [ICH: Guideline Q1A(R2) (2003), ICH: Guideline Q1D (2002)] followed by reduced stability protocols, focusing on the critical quality attributes and critical time points, being reported in the literature [Skrdla et al. (J Pharm Biomed Anal 50: 794–796, 2009)]. While the concept of lean testing is not entirely new, and it is currently a part of several regulatory guidances, it continues to evolve and gain acceptance of the industry and regulators. Methods In this review, twelve case studies are presented where stability data was collected during clinical, registration, and post-approval phases of the product development. Results Case studies summarize the lean stability testing design, the strategies applied during the regulatory filing and the outcomes of the regulatory filings. Conclusion The authors expect that the case studies presented in this review will increase the visibility of lean stability, facilitate overcoming of the existing challenges, and accelerate the global regulatory acceptance of lean stability practices in the industry.

Development and Validation of a Discriminatory Dissolution Model for an Immediately Release Dosage Form by DOE and Statistical Approaches - Mingkun Fu; Ellen Conroy; Michael Byers; Lakshminarasimhan Pranatharthiharan; Thierry Bilbault (AAPS PharmSciTech, 2021)

Development of SNP markers for the bighead carp (Hypophthalmichthys nobilis) by using transcriptomic sequences - Rui An; Jianjun Fu; Bingjie Jiang; Wenbin Zhu; Lanmei Wang; Mingkun Luo; Zaijie Dong (Conservation Genetics Resources, 2020)